Pengaruh Penambahan Variasi KJ-CTAB Terhadap Karakteristik ZnO/KJ-CTAB yang Disintesis Menggunakan Metode Impregnasi Basah: Effect of Adding KJ-CTAB Variations Towards Characteristics of Synthesized ZnO/KJ-CTAB Using Wet Impregation Method - Azzalina Nur Alviana; Aulia Dewi Rosanti; Rizky Arief Shobirin; Fahmi Hidayat (KOVALEN: Jurnal Riset Kimia, 2023)
Semiconductor photocatalysts have great potential in solving environmental problems. The photocatalyst process using a semiconductor is one of the technology to oxidize organic compounds such as dyes. Orange peel (KJ) is one of the adsorbents that have the potential for purification of dyes that increase the photocatalytic activity of ZnO material. This study aims to determine the optimum variation of KJ-CTAB to be added to ZnO material. The results of the synthesis of ZnO/KJ-CTAB varasis 1:25, 2:25, and 3:25 (w/v) using the wet impregnation method were characterized on IR, XRD, SEM, DR-UV, and BET instruments. The results showed that FTIR also showed the presence of ZnO bonds in all samples, C-H in samples varied from 1:25, 2:25, and 3:25 (w/v). The XRD results showed that the percentage of crystallinity decreased and the SEM results showed that ZnO/KJ-CTAB 1:25 had a more homogeneous morphology. Based on the results of DR-UV ZnO/KJ-CTAB 1: 25 (w/v) has a band gap energy value of 3.20 eV which is good for use in photocatalyst processes. BET results show that all samples belong to the mesoporous size.